1986
DOI: 10.3109/00365528609003087
|View full text |Cite
|
Sign up to set email alerts
|

Relations between Circulating Gastrin and Endocrine Cell Proliferation in the Atrophic Gastric Fundic Mucosa

Abstract: It has been suggested that gastrin may be a causative factor in the proliferation of gastric fundic mucosal endocrine cells, as seen in the Zollinger-Ellison syndrome and in atrophic gastritis with hypergastrinemia of antral origin. In the present study, morphometrically determined densities of endocrine cells in fundic mucosal biopsy specimens were related to basal levels of serum gastrin in 10 normal controls and 60 patients with achlorhydric fundic atrophic gastritis, of which 45 had pernicious anemia (5 wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
58
1
4

Year Published

1987
1987
2015
2015

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 127 publications
(64 citation statements)
references
References 17 publications
1
58
1
4
Order By: Relevance
“…Multicentric ECL cell carcinoids occur predominantly in two conditions, PA 20,28,29 and ZE with MEN-1 30 but are rare in sporadic ZE, 17 despite high gastrin and modest ECL cell proliferation. 12,16,17,30 There are several potential sources for elevated serum CgA in ZE, principally G cells comprising the tumour and the gastric ECL cells that proliferate in response to the tumour-related hypergastrinaemia.…”
Section: Discussionmentioning
confidence: 99%
“…Multicentric ECL cell carcinoids occur predominantly in two conditions, PA 20,28,29 and ZE with MEN-1 30 but are rare in sporadic ZE, 17 despite high gastrin and modest ECL cell proliferation. 12,16,17,30 There are several potential sources for elevated serum CgA in ZE, principally G cells comprising the tumour and the gastric ECL cells that proliferate in response to the tumour-related hypergastrinaemia.…”
Section: Discussionmentioning
confidence: 99%
“…In these patients, basal serum gastrin levels should be determined and are always elevated [11, 28, 29], as well as serum chromogranin A levels [30]. Further tests should be performed depending on the clinical context.…”
Section: Diagnostic Procedures: Imaging Nuclear Medicine and Laboratmentioning
confidence: 99%
“…Naturally occurring gastrins (G171, G1711, G3411) were several times more potent than pentagastrin in their trophic effects on normal mucosa (Johnson, 1977). More recently it was shown that the density of fundic mucosal endocrine cells was positively related to levels of serum gastrin (Borch et al, 1986).…”
mentioning
confidence: 99%